2010
DOI: 10.1590/s0100-39842010000500006
|View full text |Cite
|
Sign up to set email alerts
|

A importância do diagnóstico por imagem na classificação dos endoleaks como complicação do tratamento endovascular de aneurismas aórticos

Abstract: OBJECTIVE: To describe a series of endoleak cases and their respective classification. MATERIALS AND METHODS: The authors developed a retrospective study of endoleaks diagnosed at their institution in the period between 2005 and 2009. Twenty cases were included to illustrate the different types of endoleaks. RESULTS: Seventy percent of the patients were men, and the ages ranged from 43 to 91 years (mean, 76.3 years). Thirteen cases were observed in the infrarenal abdominal aorta, four in the thoracic aorta, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…The prevalence of AAA was 0.6% for 10 A diagnosis of AAA was more frequent among male patients (71.4%), in agreement with the literature. [1][2][3][4][5][6][7][8][9]17,22,[30][31][32] The mean diameter of the AAAs was 4 cm (range: 3.1 cm to 6.9 cm), which is similar to two other Brazilian studies, which found mean diameters of 3.9 cm 9 and 3.5 cm. 16 Elective treatment of AAAs is recommended when their diameter reaches 5.5 cm.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The prevalence of AAA was 0.6% for 10 A diagnosis of AAA was more frequent among male patients (71.4%), in agreement with the literature. [1][2][3][4][5][6][7][8][9]17,22,[30][31][32] The mean diameter of the AAAs was 4 cm (range: 3.1 cm to 6.9 cm), which is similar to two other Brazilian studies, which found mean diameters of 3.9 cm 9 and 3.5 cm. 16 Elective treatment of AAAs is recommended when their diameter reaches 5.5 cm.…”
Section: Discussionsupporting
confidence: 83%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]22,23,[30][31][32] While the 60.6% of the sample were CTs of female patients, there was a predominance (although not a statistically significant difference) of diagnoses among males [15 (60%) men and 10 (40%) women].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations